Gene signature-MELD score and alcohol relapse determine long-term prognosis of patients with severe alcoholic hepatitis - Deltenre, Pierre (Liver Int, 2019)
BACKGROUND: The gene-signature-MELD (gs-MELD) score has been shown to be a strong predictor of 6-month survival in severe alcoholic hepatitis (AH). Currently, only a few studies have evaluated the long-term prognosis of patients with severe AH. AIM: To assess the prognostic value of the gs-MELD score at 5 years in patients with severe AH. METHODS: Forty-eight consecutive patients with AH (25 males, median age 52 years [95% IC: 48–56]) were included. RESULTS: The median gs-MELD score was 2.6 (95% CI: 2.2–3.0). According to the gs-MELD score, 22 patients (46%) were considered to have a poor prognosis. During a median follow-up of 29 months (95% CI: 4–43), 19 patients (40%) were abstinent and 24 patients (50%) died. At 5 years, rates of survival were 61% (95% CI: 41–81) and 26% (95% CI: 11–55) in patients with low and high gs-MELD scores (p=0.001), and 81% (95% CI: 58–96) and 22% (95% CI: 10–47) in abstainers and in consumers (p<0.001), respectively. In multivariable competing risk regression modeling, gs-MELD score (subdistribution hazard ratio: 5.78, 95% CI:2.17–15.38, p<0.001) and recurrent alcohol consumption (subdistribution hazard ratio: 12.18, 95% CI:3.16–46.95, p<0.001) were independently associated with 5-year mortality. CONCLUSIONS: Both gs-MELD score and alcohol consumption drive AH long-term prognosis. The gs-MELD score may guide the development of molecularly targeted therapies in AH.